2014
DOI: 10.1016/j.hrthm.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Coronary sinus biomarker sampling compared to peripheral venous blood for predicting outcomes in patients with severe heart failure undergoing cardiac resynchronization therapy: The BIOCRT study

Abstract: Background-A significant minority of patients receiving cardiac resynchronization therapy (CRT) remain non-responsive to this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
1
39
0
4
Order By: Relevance
“…There is significant potential to develop and incorporate single and multimarker strategies to better risk stratify and treat patients with arrhythmias and resynchronization. Our recent work [131] on multimarker strategies has begun influencing our practice, but much of it still needs validation in prospective randomized studies.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant potential to develop and incorporate single and multimarker strategies to better risk stratify and treat patients with arrhythmias and resynchronization. Our recent work [131] on multimarker strategies has begun influencing our practice, but much of it still needs validation in prospective randomized studies.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, the source of circulating sST2 in cardiac disease was presumed to be myocardial following in vitro data showing load induction of ST2 mRNA in neonatal rat cardiac myocytes [48]. More recent work, however, suggests that in human cardiac disease, the vascular endothelial cells might be the predominant source of sST2, rather than the human myocardium [93,94,157].…”
Section: Biology Of Sst2mentioning
confidence: 99%
“…Therefore, in this part of the study, we tried to understand the role of serum Gal-3 in AF patients after establishing its effects in cellular and animal models. A recent clinical trial suggested that coronary sinus sampling of HF biomarkers, such as Gal-3, may be more appropriate than peripheral venous blood levels for predicting the outcome of cardiac resynchronization therapy [15]. Thus, we compared the levels of coronary sinus serum Gal-3 in patients who underwent pure mitral valve cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%